Dynamical Analysis of the Hd 169142 Planet-Forming Disk: Twelve Years of High-Contrast Polarimetry - Perez-Marquez, S (American Astronomical Society, 2025)
We present a dynamical analysis of the HD 169142 planet-forming disk based on high-contrast polarimetric imaging over a twelve-year observational period, offering insights into its disk evolution and planet–disk interactions. This study explores the evolution of scattered light features and their relationship with millimeter continuum emission. Archival visible-to-near-infrared scattered light observations from NACO, SpectroPolarimetric High-Contrast Imager for Exoplanets Research, and Gemini Planet Imager combined with new observations from SCExAO reveal persistent nonaxisymmetric structures in both the inner and outer rings of the disk. Through Keplerian image transformations and phase cross correlation techniques, we show that the azimuthal brightness variations in the inner ring follow the local Keplerian velocity, suggesting these are intrinsic disk features rather than planet-induced spirals or shadows. The motion of the outer ring is weakly detected, requiring a longer observational baseline for further confirmation. Comparing scattered light features with ALMA 1.3 mm continuum data, we find that the scattered light traces the edges of dust structures in the inner ring, indicating complex interactions and a leaky dust trap around the water–ice snowline. These findings highlight the capability of long-term monitoring of circumstellar disks to distinguish planetary influences from Keplerian disk dynamics. © 2025. The Author(s). Published by the American Astronomical Society.